Asynchronous Learning in Online English Class: Indonesian College Students’ Problems and Coping Strategies - Honesty Yonanda Ayudhia; Dwi Bayu Saputra; Rahmi Fadilah (Universitas Islam Negeri (UIN) Mataram, 2022)
Despite its prominence, research on asynchronous learning addressing students' issues and coping strategies, particularly in Indonesian EFL context remains sparse. This study aimed to address the research gap and uncover the students' issues in an asynchronous English class and how they cope with these challenges. The data were collected through questionnaire distributed to 67 students at an Indonesian university. The findings indicated certain issues that arise during asynchronous English lesson. The students found that a poor internet connection, social media distraction, a lack of interaction between students and the teacher as well as among students, and a lack of opportunities to practice English as their primary learning barriers. The findings also revealed that the activities that students took to deal with these problems, making a smart move in asynchronous English class, was effective. Despite the numerous distractions, the students strove to maintain their focus on the materials. However, as their strategies in asynchronous English class, students did not attempt to contact their teacher to inquire about the materials, and they did not establish a timeframe and learning objective. Limitations and recommendation for future research are discussed.